Review of culinary tourism development policy in Indonesia - Setyawati, Ria (Journal of Rural Tourism, 2024)
Purpose - This study examines the Indonesian government's strategies for advancing culinary tourism, focusing on initiatives like the "Indonesia Spice Up the World" program and promoting culinary destinations such as Bali and Yogyakarta.Methodology/Design/Approach - The study analyzes initiatives by the Ministry of Tourism and Creative Economy (Kemenparekraf) and compares Indonesia's efforts with neighboring countries like Hong Kong and Singapore, which have successfully leveraged food for tourism.Findings - Despite efforts, Indonesia has yet to fully establish itself as a global culinary tourism leader. Challenges include integrating food into broader tourism strategies, improving chef competence, and developing policies that address the entire food supply chain.Originality/Value - The study advocates for a comprehensive approach to culinary tourism that links food with national development policies, strengthens chef skills, and extends efforts to rural areas to preserve traditions and promote sustainable tourism.